Treatments for elderly cancer patients and reforms to social security systems in Japan - Nagashima, Fumio; Furuse, Junji (International journal of clinical oncology, 2022)
In Japan, the population aged 65 years and above accounts for 29% of the total population. Furthermore, the number of cancer patients among the elderly is increasing. Geriatric oncology is a discipline that deals with appropriate care for elderly cancer patients based on their characteristics. The International Society of Geriatric Oncology considers education, treatment, research, and partnership building areas of significance and priority for policy goals. In Japan, the Third Term of the Basic Plan to Promote Cancer Control is an initiative to improve the infrastructure and health services involved in cancer care. Content related to “cancer in the elderly” was added to establish guidelines for treating cancer in the elderly. Thus far, “Clinical Practice Guidelines of Cancer Drug Therapies for the Elderly” have been published. With the increasing age of the population, social security expenditures will increase substantially after the fiscal year 2022. Reforms to social security systems, such as pensions, medical care, and nursing care, are underway. It is important to enhance cooperation between oncology and geriatrics and to support cooperative systems among families and medical professionals to promote geriatric oncology. Since the working-age population and the total population have begun to decline, Japan is facing many challenges. As a leader of a super-aging society, Japan has the potential to share its experience on a global scale and address potential long-term outcomes.